Pentingnya Visi Dan Misi Dalam Mengelola Suatu Usaha - Djaka Suryadi (Jurnal Asy-Syukriyyah, 2012)
Vision and Mission are two words that have a meaning which, vision is a desire of individuals / institutions of the state of the future desired / aspired to by the individual / all members of your organization in all levels of management while the Mission One level of effort, thought, step - step formally to create a mission, meant to clarify what action is desired by the owner of your company and be a handle to run your business now into the foreseeable future until the vision is realized. Vision and Mission is a guide line of work in running the business effectively and efficiently to achieve maximum results, which must be obeyed and executed all line management level, which in turn is expected to be a corporate culture of a business.